Proyecto de factibilidad para la creación de una empresa de servicios de asesoría financiera, tributaria, administrativa y gestión de riesgo integral en la ciudad de Manta, Manabí - Ganchozo Lucas, Christian José (2015)
This project focuses on the study of market, technical and financial that will allow you to determine the feasibility for the creation of the company "GALU CONSULTANCY SERVICES E. U. R. L. ". The company will be responsible for providing financial advisory services, tax, administrative and Comprehensive Risk Management in the city of Manta-Manabí, will be responsible for providing the advice mentioned to the SMES affiliated the Superintendence of Companies. In the first chapter develops the conceptual framework, these concepts will be the fundamental basis for the development of the thesis work. In the second chapter is made the legal study, determines the organizational structure of the company. In the third chapter is made the respective market research, analyzing its components such as demand, supply and the mix of Marketing: price, promotion, product and plaza, in addition to the distribution channels. In the fourth chapter is made the technical study, which determines the location conducive to establish the company's facilities, in addition is determined human resources, materials, financial and economic requirements for the operation of the company. In the fifth chapter presents the study economic and financial evaluation, where is the stable amount of resources required to implement the project, the total cost of the operation, the different operational costs and a series of financial indicators that will serve as a basis for determining the feasibility and implementation of the project under study. Finally, we present the findings, while at the same time there are recommendations that can become viable guidelines for the implementation of the proposal.